2019
DOI: 10.1103/physrevx.9.011017
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Dynamics of Janus Oscillator Networks

Abstract: Recent research has led to the discovery of fundamental new phenomena in network synchronization, including chimera states, explosive synchronization, and asymmetry-induced synchronization. Each of these phenomena has thus far been observed only in systems designed to exhibit that one phenomenon, which raises the questions of whether they are mutually compatible and, if so, under what conditions they co-occur. Here, we introduce a class of remarkably simple oscillator networks that concurrently exhibit all of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…By employing the scheme provided by the OA ansatz, we obtained, for random regular networks, a reduced set of equations whereby critical points of the dynamics were revealed. We found that several collective behaviors coexist for intermediate coupling values, elucidating the findings in [6]. Although initially obtained for homogeneous networks, we verified that the solutions of the reduced system fitted ac-curately numerical experiments for dense ER networks.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…By employing the scheme provided by the OA ansatz, we obtained, for random regular networks, a reduced set of equations whereby critical points of the dynamics were revealed. We found that several collective behaviors coexist for intermediate coupling values, elucidating the findings in [6]. Although initially obtained for homogeneous networks, we verified that the solutions of the reduced system fitted ac-curately numerical experiments for dense ER networks.…”
supporting
confidence: 81%
“…All in all, we provided the first theoretical and numerical analysis of ensembles of Janus oscillators on homogeneous and heterogeneous random networks. As such, our work raises further interesting questions about the study initiated by Nicolaou et al [6]. For instance, future investigations should target the dynamics on sparse and correlated networks -situations in which the ensemble approach in [10] and mean-field techniques are inaccurate in predicting tipping points of the system -as well as limitations of the OA manifold in capturing the Janus dynamics.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…A natural direction of future work would involve studying the effects of more recent synchronization techniques like Janus oscillators (Nicolaou et al, 2019) shown to concurrently handle phenomena like network synchronization and asymmetry-induced synchronization for scenarios with (a) explosive synchronizations and (b) extreme multi-stability of chimaera states. Further, use of Quantum Neural Networks (Narayanan and Menneer, 2000) might provide enhanced predictive power for better leader-follower estimation in our architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Equipping swarmalators with these features would likely cure the poverty of phenomena in the first, third, and fourth quadrants of the (J, K) plane ( Figure 2) and produce new dynamics in Iswasa-tanaka and Vicesek type models, too. Phase models more sophisticated than the Kuramoto model could also be explored; the Winfree model [94] or the newly introduced Janus oscillators [95] would be exciting to experiment with. Swarmalators with discrete and spatially local coupling also merit study and are useful in com-puter and communication systems.…”
Section: Discussionmentioning
confidence: 99%